Simple urine testing could avoid delay in the diagnosis of rapidly progressive glomerulonephritis. Issue 866 (December 1997) - Howse, M.; Main, J.
Abstract : Four cases of rapidly progressive glomerulonephritis are presented. In all four there was a two to three month delay between the onset of symptoms and appropriate diagnosis, referral and treatment. It is likely that simple stick testing of urine would have given a vital diagnostic clue and allowed earlier referral and treatment.